A Cu-MOF-derived N-doped porous carbon material and its preparation method and application
The N-doped porous carbon material derived from Cu-MOF was synthesized through hydrothermal reaction, and the liquid-liquid dual continuous microemulsion interface was constructed using organic alkali and surfactant, which solved the problem of uneven distribution of copper ions, improved the N-doping content and copper oxide loading, and enhanced the catalytic performance.
Patent Information
- Application Number
- CN202310313440.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-28
AI Technical Summary
In the prior art, when preparing porous carbon materials, copper ions are unevenly distributed, resulting in low element doping ratio and insufficient catalytic performance.
The Cu-MOF-derived N-doped porous carbon material is synthesized through hydrothermal reaction, and a liquid-liquid dual continuous microemulsion interface is constructed using organic alkali and surfactant to realize that metal hydroxide encapsulate HKUST-1, form a putaway structure, and increase the N-doping content and cuprous oxide load during high-temperature carbonization.
The N doping content and cuprous oxide loading are improved, the catalytic performance of the material is enhanced, and the secondary pollution caused by metal ion emissions is avoided.
Smart Images

Figure CN116532141B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to a Cu-MOF-derived N-doped porous carbon material and a preparation method and application thereof. Background Art
[0002] MOFs have been widely studied as ideal sacrificial templates for preparing a variety of carbon-based nanomaterials such as porous carbon, heteroatom-doped porous carbon, metal oxides, and porous carbon nanohybrids. These processes are usually carried out by thermal decomposition under a controlled atmosphere (such as Ar, N2, air), and materials with special morphology, structure, and properties can be obtained.
[0003] Porous carbon materials have rich pore structures and large specific surface areas, which can not only provide a more convenient material diffusion path, but also promote the adsorption of reactants. The existing methods of direct carbonization will lead to the aggregation of copper elements, uneven distribution of copper ions, and low element doping rate. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a Cu-MOF-derived N-doped porous carbon material and a preparation method and application thereof, which can achieve an increase in the N-doping content and cuprous oxide and cupric oxide loading, enhance the material's ability to activate persulfate, and improve the material's catalytic performance.
[0005] The present invention provides the following technical solutions:
[0006] In a first aspect, a method for preparing a Cu-MOF-derived N-doped porous carbon material is provided, comprising the following steps:
[0007] A mixed aqueous solution of copper nitrate and zinc nitrate is mixed with a methanol solution of trimesic acid and subjected to a hydrothermal reaction to obtain a HKUST-1 precursor solution;
[0008] Adding a surfactant to an oil phase solvent, and adding an organic base after dissolving the surfactant to obtain an oil phase solution;
[0009] The HKUST-1 precursor solution and the oil phase solution are mixed and stirred, and the solid generated by the reaction is washed and dried to obtain N-doped Zn / Cu-MOF;
[0010] The N-doped Zn / Cu-MOF is carbonized, and the carbonized product is then sequentially acid-washed, alcohol-washed and dried to obtain a Cu-MOF-derived N-doped porous carbon material.
[0011] Furthermore, the molar ratio of copper nitrate to zinc nitrate in the mixed aqueous solution of copper nitrate and zinc nitrate is (1-2):1; this ratio allows the generated MOF material to maintain its original structure relatively intact after carbonization; adding too much zinc nitrate will cause the carbon frame to collapse, and adding too little will cause uneven distribution of Cu, forming a large amount of alloy elements.
[0012] The ratio of the sum of the molar concentrations of copper nitrate and zinc nitrate in the mixed aqueous solution of copper nitrate and zinc nitrate to the molar concentration of trimesic acid in the methanol solution of trimesic acid is (1.7-2):1.
[0013] Furthermore, the temperature of the hydrothermal reaction is 110-150° C., the reaction time is 18-36 hours, and the reaction generates a blue powdery substance. If the temperature is too high or the reaction time is too long, a black carbonaceous substance will be generated, reducing the yield.
[0014] Furthermore, the surfactant includes one of Tween 60, Tween 80, DDAB, CTAB, and DTAB; the oil phase solvent includes monobromotetradecane or dodecane; and the organic base includes one of benzylamine, triethylamine, and urea.
[0015] Furthermore, the concentration of the surfactant in the oil phase solution is (60-70) g / L, and the surfactant provides a carbon source for the reduction of copper oxide and zinc oxide. If the surfactant concentration is too low, some metal oxides will remain, and too much cuprous oxide will be reduced, resulting in a poor catalyst effect. Moreover, the addition of surfactants will successfully dope the nitrogen in the benamine. Low concentrations will result in the benamine not being completely hydrolyzed and not being fully doped into the MOF. The concentration of the surfactant in the mixture of the HKUST-1 precursor solution and the oil phase solution is (20-25) g / L. Too much surfactant cannot ensure that all the remaining divalent copper ions in the MOF reaction process are fully hydrolyzed to generate metal hydroxides, and there will be excess organic bases, resulting in the added chemicals not being fully utilized.
[0016] Furthermore, after the HKUST-1 precursor solution and the oil phase solution were mixed, they were magnetically stirred for 24 hours, and the solid generated by the reaction was washed with ethanol three times and then vacuum dried at 80° C. for 24 hours.
[0017] Furthermore, the carbonization temperature is 800-1000° C. and the time is 3-5 hours.
[0018] Furthermore, the carbonized product is soaked in an acid solution with a concentration of 0.1 to 1 mol / L for 10 hours for acid washing, and then soaked in an alcohol solution for 10 hours for alcohol washing.
[0019] In a second aspect, a Cu-MOF-derived N-doped porous carbon material prepared by the method described in the first aspect is provided.
[0020] In a third aspect, there is provided an application of the Cu-MOF-derived N-doped porous carbon material described in the second aspect in degrading organic pollutants and catalyzing carbon dioxide conversion.
[0021] The reaction mechanism for preparing Cu-MOF-derived N-doped porous carbon materials in the present invention is:
[0022] First, a mixed aqueous solution of copper nitrate and zinc nitrate is mixed with a methanol solution of trimesic acid and subjected to a hydrothermal reaction to obtain a copper organic framework compound (HKUST-1) precursor solution. Due to the limitations of the reaction conditions, some metal ions will remain. Then, an organic base is added to the precursor solution, and under the action of a surfactant, a liquid-liquid bicontinuous microemulsion interface is formed. At this interface, the organic base encounters the aqueous solution and hydrolyzes to generate OH with a certain amount. - , OH - It quickly forms hydroxide precipitates with metal ions in the aqueous solution, and under the action of magnetic stirring and ultrasound, a mixture of metal hydroxide-encapsulated metal organic framework Cu(OH)2@HKUST-1 is formed. At the same time, the surfactant and the generated particulate matter form new micelles, which promote the bicontinuous microemulsion to use the new micelles as templates to further generate encapsulated particles, successfully doping the N element into the particles and consuming the metal ions in the solution as much as possible, converting the metal ions into solids as much as possible; finally, metal elements, metal single atoms, and metal oxide-loaded nitrogen-doped porous carbon particles are generated under carbonization pyrolysis conditions.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention obtains HKUST-1 through a hydrothermal reaction, takes HKUST-1 as the core, and constructs a liquid-liquid bicontinuous microemulsion interface by adding an organic base and a surfactant, so that the metal hydroxide wraps HKUST-1 to form a core-shell structure, and further through high-temperature carbonization, while preserving the HKUST-1 carbon skeleton, the N doping content is increased and the cuprous oxide and cupric oxide loading are achieved, and the secondary pollution caused by the discharge of metal ions during the material preparation process is avoided;
[0025] (2) The Cu-MOF-derived N-doped porous carbon material prepared by the present invention realizes the doping of metal elements, metal atoms, metal oxides and N elements at the same time, which can provide more oxygen vacancies and atomic defects for the carbon material, thereby obtaining better catalytic performance;
[0026] (3) The Cu-MOF-derived N-doped porous carbon material prepared by the present invention is rich in cupric oxide and cuprous oxide, and can be used as an activator for persulfate. The large specific surface area of its porous structure not only has excellent adsorption performance, but the vacancies and defects on the surface of the material can also quickly activate persulfate, thereby achieving the effect of degrading organic pollutants. In addition, because the material also contains metallic copper, it can generate Cu-N4, which can catalyze the conversion of carbon dioxide and achieve carbon neutrality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of the HKUST-1 precursor solution in Example 1 of the present invention;
[0028] Figure 2 is a SEM image of the N-doped porous carbon material derived from Cu-MOF in Example 1 of the present invention;
[0029] Figure 3 is the XRD pattern of the Cu-MOF-derived N-doped porous carbon material in Example 1 of the present invention;
[0030] Figure 4 is a surface scan of the N-doped porous carbon material derived from Cu-MOF in Example 1 of the present invention;
[0031] Figure 5 is a SEM image of the N-doped porous carbon material derived from Cu-MOF in Comparative Example 1 of the present invention;
[0032] Figure 6 is a SEM image of the HKUST-1 precursor solution in Example 2 of the present invention;
[0033] Figure 7 It is a diagram showing the effect of removing PNP by activating persulfate in the application example of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0037] (1) Preparation of HKUST-1 precursor solution
[0038] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L copper nitrate and zinc nitrate mixed aqueous solution (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, put it into a blast drying oven after ultrasonic treatment for 15 minutes, and hydrothermally react at 125°C for 24 hours. Transfer the resulting solution into a conical flask, i.e., the HKUST-1 precursor solution. Figure 1 The SEM image shows a regular octahedron, which is the standard HUKST-1 structure.
[0039] (2) Preparation of N-doped Zn / Cu-MOF
[0040] 1.6 g of DDAB was added to a centrifuge tube, and 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0041] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0042] The N-doped Zn / Cu-MOF solid was transferred into a tube furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the surface elemental Zn and metal oxides, and washed with ethanol to remove the surface organic matter, and dried to obtain Cu-MOF-derived N-doped porous carbon material. Figure 2 , 3 and 4 are its SEM, XRD and surface scanning EDS images respectively. Figure 2 As shown, it is a porous material structure; Figure 3 XRD shows that Cu peak and Cu2O peak appear, and a typical peak appears at 2θ=26°, which is the 002 crystal plane of graphite carbon; Figure 4 EDS shows that C and N are evenly distributed on the surface of the material, and Cu is also evenly distributed on the surface of the material.
[0043] Example 2
[0044] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0045] (1) Preparation of HKUST-1 precursor solution
[0046] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L copper nitrate and zinc nitrate mixed aqueous solution (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, put it into a blast drying oven after ultrasonic treatment for 15 minutes, and hydrothermally react at 125°C for 24 hours. Transfer the resulting solution into a conical flask, i.e., the HKUST-1 precursor solution. Figure 6 The SEM image is shown in Figure 2. Figure 1 The same is a standard octahedral structure, indicating that HKUST-1 was successfully synthesized.
[0047] (2) Preparation of N-doped Zn / Cu-MOF
[0048] 1.6 g of Tween-60 was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0049] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0050] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0051] Example 3
[0052] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0053] (1) Preparation of HKUST-1 precursor solution
[0054] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0055] (2) Preparation of N-doped Zn / Cu-MOF
[0056] 1.6 g DTAB was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0057] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0058] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0059] Example 4
[0060] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0061] (1) Preparation of HKUST-1 precursor solution
[0062] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0063] (2) Preparation of N-doped Zn / Cu-MOF
[0064] 1.6 g CTAB was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0065] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0066] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0067] Example 5
[0068] (1) Preparation of HKUST-1 precursor solution
[0069] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0070] (2) Preparation of N-doped Zn / Cu-MOF
[0071] 1.6 g DDAB was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of triethylamine solution was added, and ultrasonication was performed for 30 seconds. The oil phase solution was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The rotor was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0072] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0073] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0074] Example 6
[0075] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0076] (1) Preparation of HKUST-1 precursor solution
[0077] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 minutes, put it into a forced air drying oven, hydrothermally react at 125°C for 24 hours, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0078] (2) Preparation of N-doped Zn / Cu-MOF
[0079] 1.6 g DDAB was added to a centrifuge tube, 23 ml dodecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml benzylamine solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0080] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0081] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0082] Example 7
[0083] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0084] (1) Preparation of HKUST-1 precursor solution
[0085] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0096 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 2:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, put it into a forced air drying oven after ultrasonic treatment for 15 minutes, and perform hydrothermal reaction at 125°C for 24 hours to generate a HKUST-1 precursor solution, which is then transferred to a conical flask.
[0086] (2) Preparation of N-doped Zn / Cu-MOF
[0087] 1.68 g of DDAB was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0088] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0089] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0090] Example 8
[0091] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0092] (1) Preparation of HKUST-1 precursor solution
[0093] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0087 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1.5:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0094] (2) Preparation of N-doped Zn / Cu-MOF
[0095] 1.44 g of DDAB was added to a centrifuge tube, and 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0096] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0097] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0098] Example 9
[0099] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0100] (1) Preparation of HKUST-1 precursor solution
[0101] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 110 ° C for 36 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0102] (2) Preparation of N-doped Zn / Cu-MOF
[0103] 1.6 g of DDAB was added to a centrifuge tube, and 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of urea solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0104] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0105] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 800°C for 5 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0106] Example 10
[0107] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0108] (1) Preparation of HKUST-1 precursor solution
[0109] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 150 ° C for 18 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0110] (2) Preparation of N-doped Zn / Cu-MOF
[0111] 1.6 g of DDAB was added to a centrifuge tube, and 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of urea solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0112] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0113] The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 900°C for 4 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Cu-MOF-derived N-doped porous carbon material.
[0114] Comparative Example 1
[0115] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0116] (1) Preparation of HKUST-1 precursor solution
[0117] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 0.0084 mol / L copper nitrate aqueous solution; transfer the above solutions into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, and hydrothermally react at 125 ° C for 24 h to generate a HKUST-1 precursor solution, which is then transferred to a conical flask.
[0118] (2) Preparation of N-doped Cu-MOF
[0119] 1.6 g of DDAB was added to a centrifuge tube, and 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml of benzylamine solution was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Cu-MOF.
[0120] (3) Preparation of Cu-MOF-derived N-doped porous carbon materials
[0121] The N-doped Zn / Cu-MOF solid was transferred into a tube furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the metal oxide on the surface, and washed with ethanol to remove the organic matter on the surface, and dried to obtain the Cu-MOF-derived N-doped porous carbon material. Figure 5 The SEM image is a side view of a single body. Figure 1 Different from the intact and smooth surface, the surface has a layered structure, and there is also structural collapse due to the incorporation of organic bases, as well as pores caused by carbonization, which is similar to Figure 2 The carbonization structure is also different, which means that not adding zinc will make the carbonization structure different and look more delicate.
[0122] Comparative Example 2
[0123] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0124] (1) Preparation of HKUST-1 precursor solution
[0125] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 0.0084 mol / L zinc nitrate aqueous solution; transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, put it into a forced air drying oven after ultrasonic treatment for 15 minutes, and hydrothermally react at 125°C for 24 hours to generate a MOF-Zn precursor solution, which is then transferred to a conical flask.
[0126] (2) Preparation of N-doped Zn-MOF
[0127] Take 1.6g CTAB and add it to a centrifuge tube, add 23ml of monobromotetradecane solution, ultrasonically dissolve it to generate a transparent colorless solution, add 1ml of benzylamine solution, ultrasonicate for 30 seconds, mix it thoroughly and evenly to obtain an oil phase solution; pour the oil phase solution into the Zn-MOF precursor solution, ultrasonicate for 30 minutes, add a rotor, and magnetically stir it for 24 hours. The generated solid is washed three times with ethanol, and vacuum dried at 80°C for 24 hours to obtain N-doped Zn-MOF.
[0128] (3) Preparation of Zn-MOF-derived N-doped porous carbon materials
[0129] The N-doped Zn-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C for 3 h under N2 conditions with a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain Zn-MOF-derived N-doped porous carbon material.
[0130] Comparative Example 3
[0131] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0132] (1) Preparation of HKUST-1 precursor solution
[0133] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0134] (2) 1.6 g DDAB was added to a centrifuge tube, 23 ml of monobromotetradecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 0.37 g NaOH was added, and ultrasonication was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonication for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0135] (3) The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 1000°C under N2 conditions for 3 h at a heating rate of 5°C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain the material.
[0136] Comparative Example 4
[0137] This embodiment provides a method for preparing a Cu-MOF-derived N-doped porous carbon material, the steps are as follows:
[0138] (1) Preparation of HKUST-1 precursor solution
[0139] Prepare 24 ml of 0.0048 mol / L 1,3,5-trimethylbenzenecarboxylic acid methanol solution; prepare 24 ml of 0.0084 mol / L mixed aqueous solution of copper nitrate and zinc nitrate (the molar ratio of copper nitrate to zinc nitrate is 1:1); transfer the above solution into a 150 ml polytetrafluoroethylene reactor for mixing, ultrasonicate for 15 min, put it into a forced air drying oven, hydrothermally react at 125 ° C for 24 h, and transfer the generated HKUST-1 precursor solution to a conical flask.
[0140] (2) Preparation of N-doped Zn / Cu-MOF
[0141] 1.6 g DDAB was added to a centrifuge tube, 23 ml dodecane solution was added, and ultrasonic dissolution was performed to generate a transparent colorless solution. 1 ml benzylamine solution was added, and ultrasonic treatment was performed for 30 seconds. The mixture was fully mixed to obtain an oil phase solution. The oil phase solution was poured into the HKUST-1 precursor solution, and a rotor was added after ultrasonic treatment for 30 minutes. The mixture was magnetically stirred for 24 hours. The generated solid was washed three times with ethanol and vacuum dried at 80°C for 24 hours to obtain N-doped Zn / Cu-MOF.
[0142] (3) The N-doped Zn / Cu-MOF solid was transferred into a tubular furnace and carbonized and pyrolyzed at 700 °C for 3 h under N2 conditions with a heating rate of 5 °C / min. The sample was taken out and washed with 1 mol / L HCl solution to remove the elemental Zn and metal oxides on the surface. The organic matter on the surface was washed with ethanol and dried to obtain the material.
[0143] Application Examples
[0144] Take 0.02g of the final material prepared in Examples 1 to 10 and Comparative Examples 1 to 4 and put it into 100ml of 20mg / L p-nitrophenol (PNP) solution. Put it into a constant temperature shaker, shake it at 200r / min for 1h, then add persulfate, add 0.5mmol persulfate and continue shaking for 1h. Take samples once every half an hour for the first hour, and every 15min for the last hour, and calculate the concentration of PNP in the solution. Test the ability of the material to activate persulfate, the results are as follows: Figure 7 As shown in Table 1. Figure 7 From Table 1, we can see that:
[0145] (1) When copper and zinc are used as metal salts, DDAB surfactant is used as a carbon source, which can make the material have better adsorption performance, excellent catalytic effect, and less metal ion leaching. The material of Example 1 adsorbs 60%, and the degradation effect of pollutants is basically more than 90% after 15 minutes of degradation; when there is no zinc in the metal salt solution of the precursor (Comparative Example 1), 97% of the pollutants can be degraded in 2 hours, and the effect becomes worse, but more metal ions are leached; when there is no copper in the metal salt solution of the precursor (Comparative Example 2), after high temperature and acid washing and alcohol washing, only nitrogen-doped carbon materials are left, and the adsorption effect is not good. However, after catalyzing persulfate, the removal rate of pollutants can reach more than 80%, the adsorption effect is relatively poor, the catalytic effect is general, and the pollutants cannot be completely removed.
[0146] (2) When Tween-60 (Example 2), DTAB (Example 3), and CTAB (Example 4) are used as carbon sources, the adsorption effect of the catalyst is less than 20%. However, after catalysis, the difference is very large. When Tween-60 is used as a surfactant, the PNP removal efficiency can reach 100%, and CTAB and DTTAB can reach about 70%.
[0147] (3) When no organic base is added (Comparative Example 3) and no nitrogen doping is performed, the adsorption effect can remove 30% in 1 hour, but the catalytic effect is very poor, and there is basically no catalytic effect, and the total removal rate is less than 50%. When only C exists in the system, the adsorption effect is about 10%, and the catalytic effect can reach 75%, which is better than the activation effect of general carbon materials on PMS. Different organic bases (Example 5) have little effect on the material effect. As the nitrogen content increases, the catalytic effect increases.
[0148] (4) When dodecane is used as the oil phase (Example 6), after carbonization, the carbon content becomes lower, the adsorption effect of the material becomes worse, the catalytic effect becomes better, but the amount of metal ion leaching also increases.
[0149] (5) When the carbonization temperature is too low (Comparative Example 4), the carbonization of the surfactant is not complete, the reduction reaction of the metal oxide is not complete, and Zn cannot be completely removed because it has not reached the boiling point. After cleaning and soaking, the metal turns into ions and leaves, resulting in a lower metal loading and poorer adsorption and catalytic effects.
[0150] (6) Since the active sites of the catalyst are mainly concentrated in the Cu element and its oxide nitride, the copper doping amount in the catalyst raw material is increased (Examples 1, 7, and 8), exposing more active sites, but the metal ion leaching will also increase. However, compared with the undoped material, the leaching amount is reduced and the catalytic effect is improved.
[0151] Table 1 Contents of different elements in the materials prepared in the examples and comparative examples
[0152]
[0153]
[0154] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Cu-MOF-derived N-doped porous carbon material, characterized in that: The following steps are involved: A mixed aqueous solution of copper nitrate and zinc nitrate is mixed with a methanol solution of trimesic acid and subjected to a hydrothermal reaction to obtain a HKUST-1 precursor solution; Adding a surfactant to an oil phase solvent, and adding an organic base after dissolving the surfactant to obtain an oil phase solution; The HKUST-1 precursor solution and the oil phase solution are mixed and stirred, and the solid generated by the reaction is washed and dried to obtain N-doped Zn / Cu-MOF; The N-doped Zn / Cu-MOF is carbonized, and then the carbonized product is sequentially acid-washed, alcohol-washed and dried to obtain a Cu-MOF-derived N-doped porous carbon material; The molar ratio of copper nitrate to zinc nitrate in the mixed aqueous solution of copper nitrate and zinc nitrate is (1-2):1; The organic base includes one of benzylamine, triethylamine and urea; The concentration of the surfactant in the oil phase solution is (60-70) g / L, and the concentration of the surfactant in the mixture of the HKUST-1 precursor solution and the oil phase solution is (20-25) g / L.
2. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: The ratio of the sum of the molar concentrations of copper nitrate and zinc nitrate in the mixed aqueous solution of copper nitrate and zinc nitrate to the molar concentration of trimesic acid in the methanol solution of trimesic acid is (1.7-2):
1.
3. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 110-150° C. and the time is 18-36 hours.
4. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: The surfactant includes one of Tween 60, Tween 80, DDAB, CTAB and DTAB, and the oil phase solvent includes monobromotetradecane or dodecane.
5. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: After the HKUST-1 precursor solution and the oil phase solution were mixed, they were magnetically stirred for 24 hours, and the solid generated by the reaction was washed with ethanol three times and then vacuum dried at 80° C. for 24 hours.
6. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: The carbonization temperature is 800-1000° C. and the time is 3-5 hours.
7. The method for preparing Cu-MOF-derived N-doped porous carbon material according to claim 1, characterized in that: The carbonized product is soaked in an acid solution with a concentration of 0.1~1 mol / L for 10 hours for acid washing, and then soaked in an alcohol solution for 10 hours for alcohol washing.
8. A Cu-MOF-derived N-doped porous carbon material prepared by the method according to any one of claims 1 to 7.
9. Use of the Cu-MOF-derived N-doped porous carbon material according to claim 8 in degrading organic pollutants and catalyzing carbon dioxide conversion.
Citation Information
Patent Citations
Composite electrode material and preparation method thereof, and super capacitor
CN110993368A
3D Co-MOF / Cu-coated Cu air disinfection nano composite material and preparation method thereof
CN114106569A